FORMATION OF INFORMATION LITERACY IN PRIMARY SCHOOL STUDENTS - Olimov Baxtiyorjon Usmonovich; Olimova Dilshodaxon Baxtiyorjon Qizi (Scholar Express Journal, 2021)
The article contains views on the knowledge of primary school students, to organize lessons using widely used computer technology, resulting in the resulting effective knowledge.
Keywords: Education; upbringing; information and communication technologies; exhibitions